IT auditing in institutes of higher learning / Jasber Kaur Gian Singh and Yap May Lin - Gian Singh, Jasber Kaur; Yap, May Lin (University Publication Centre (UPENA), 2007)
Information technology (IT) has become an essential tool for businesses in performing daily operations and processes. Realizing this fact, business practitioners must make sure that business information transmitted via the IT medium is kept confidential with the integrity and availability of information resources being well preserved (Posthumus & von Solms, 2004), Numerous threats and vulnerabilities exposed in using IT have posed concerns over issues like confidentiality, integrity and availability. One way to ensure that business information retains its value is through the conduct of IT auditing. The same scenario of the pervasiveness of IT may be witnessed in the education sector where the traditional classroom teaching and learning process is not only strongly supported by IT tools but in the case of electronic learning (e-learning), vast amounts of IT tools coupled with Internet technology are used to facilitate and enhance the learning process. And, just as in the business sector, there is the need for IT audit in the academic sector as academic institutions increasingly employ the use of IT to carry out its organization processes. Literature in the area of IT audit in academic institutions, particularly in Malaysia, is very scarce despite intensive IT advancement in this sector. A study on IT audit practice in Malaysian institutes of higher learning (IHLs) was conducted. This paper reports on the study which was conducted to determine IT audit practices in the IHLs, focusing on those with MSC status located within the Klang Valley region. The primary data was collected through the use of questionnaires in interviews as well as distributed to IT personnel from each IHL A five-point Likert scale (of very significant, significant, moderate, least significant and not significant) was also used in this questionnaire to determine factors influencing the use of IT audit. Out of 29 IHLs, 15 questionnaires were collected and analyzed. The results of the study indicated that the level of IT auditing in IHL is satisfactory (71%) with most of the respondents reporting positively to conducting IT audit in their premises, either annually or bi-annually, and with a few even practicing compliancy to some standards. This study further determines some influential factors in IT audit implementation in IHLs. Findings from the study indicate that the significant factors are (from most to least significant): IT infrastructure, system performance, security support, organization compliance and top management support.